ОСНОВНЫЕ НАПРАВЛЕНИЯ И ПРИНЦИПЫ ФОРМИРОВАНИЯ ТОЛЕРАНТНОСТИ ДОШКОЛЬНИКОВ - Бекманова, Ж.А.; Калыбаева, А.Е. (SCIENCE and SOCIETY, 2025)
An important task of the education system - the formation of individual tolerance - requires the creation of an effective pedagogical system that effectively influences the development of this quality, starting from preschool age.
Keywords: tolerance; dialogue of cultures; preschoolers; pilot experiment; analysis; problems; play activities; art; factors; principles; integration; vitality; creativity